2020
DOI: 10.9734/ajmah/2020/v18i1030256
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic and Nutritional Status Correlates in Pulmonary Tuberculosis Patients in Calabar, Nigeria

Abstract: Introduction: Tuberculosis (TB) continues to rank high in contributing to the global disability adjusted life years with 10 million new cases yearly worldwide. Having effective control of TB particularly in endemic communities should be predicated on understanding factors that drive its upsurge. Objectives: This study assessed the association between socio-demographic factors and nutritional status among adults with pulmonary TB in Calabar, Nigeria. Methods: A descriptive analysis of a randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Low income was statistically significantly associated with low mammography uptake in this study, which is not entirely surprising as income and financial factors have been implicated as huge barriers to utilization of healthcare services [ 6 , 14 , 15 , 17 , 18 , 25 , 29 , 31 ]. In addition, substantial number of Nigerians live below the poverty line with little disposable income to get by, playing out in a cumulative manner to financial incapability and inequities in access to healthcare [ 3 , 6 , 11 , 16 ].…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Low income was statistically significantly associated with low mammography uptake in this study, which is not entirely surprising as income and financial factors have been implicated as huge barriers to utilization of healthcare services [ 6 , 14 , 15 , 17 , 18 , 25 , 29 , 31 ]. In addition, substantial number of Nigerians live below the poverty line with little disposable income to get by, playing out in a cumulative manner to financial incapability and inequities in access to healthcare [ 3 , 6 , 11 , 16 ].…”
Section: Discussionsupporting
confidence: 58%
“…The overall low uptake of mammography in this study ties closely to the high proportion of respondents that reported lack of knowledge about mammography as a major barrier to uptake. This thus presents justification why awareness about breast cancer should be at the core of its control programmes [ 12 , 16 , 18 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations